KREATIVITAS PEMBINA SEKAMI KEUSKUPAN AGUNG KUPANG - Oetpah, Dorince; Tukan, Antonius I. Nggino; Manao, Rosalia Melani; Rara, Pula Afra Deran; Mataufina , Maria Roswita; Wea, Maria Elvina; Uay, Helena Lina (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2022)
The aim of this research is to find a general profile of the creativity of SEKAMI Trustees of the Archdiocese of Kupang. This research was born from the author's concern regarding the importance of the Church's attention to the formation of children's faith. One of the tasks that the Church can do is to help develop children's faith. This research uses descriptive-quantitative methods. This method attempts to describe the situation or reality in the form of percentage figures. To obtain accurate data, the author shares that the results of the research show that the creativity of SEKAMI supervisors in the Kupang Archdiocese (especially in the respondent's area) is classified as very good. 129 SEKAMI coaches out of 152 respondents stated that they were very creative in carrying out their duties and calling. The score obtained for the aspect of self-awareness as a SEKAMI coach was 91.4%. For the aspect of creativity in thinking and acting, a score of 86.8% was obtained. Meanwhile, for the aspect of the relationship between designed or planned activities and parish pastoral care, a score of 61.8% was obtained.